The Spectrum of Maculopathy in Mitochondrial DNA A3243G Mutation: A Case Series of Six Patients - Kaisari, Eirini; Borruat, François-Xavier (Klinische Monatsblätter für Augenheilkunde, 2021)
Background The mitochondrial DNA (mtDNA) A3243G point mutation encompasses a heterogenous group of disorders including mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS), maternally inherited diabetes and deafness (MIDD), and, rarely, chronic progressive external ophthalmoplegia (CPEO). Regardless of the clinical phenotype, a specific retinopathy has been associated with the presence of this mitochondrial DNA mutation. We present six female patients exhibiting retinopathy of the A3243G point mutation at various stages.History and Signs Six female patients (37 – 70 years old) with the A3243G point mutation (four MELAS, one MIDD, and one CPEO) exhibited a maculopathy. Visual acuity ranged from 1/60 to 10/10. Visual field abnormalities varied from minimal decreased sensitivity to absolute central scotomas. They all exhibited, at various degrees, a characteristic pattern of perimacular and peripapillary retinal pigment epithelium (RPE) alterations, with mottled dys-autofluorescence and RPE atrophy and deposits on OCT.Therapy and Outcome The level of visual impairment depended on the foveal involvement and the extension of RPE atrophy. The severity of the maculopathy was not related to age. In the only long-term follow-up (15 years), evolution was slowly progressive.Conclusions A single mtDNA point mutation at locus 3243 can result in a variety of clinical presentations (MELAS, MIDD, or CPEO). Ocular involvement may manifest as a perimacular/peripapillary RPE atrophy/deposit, which can variably impact central visual function (from asymptomatic to legal blindness). The discovery of such a maculopathy should prompt the ophthalmologist to complete the personal and family history, namely, asking for the presence of diabetes mellitus and/or deafness.
Keywords: A3243G; MELAS; MIDD; mitochondriopathies; maculopathy